Analisis Kadar Alkohol Pada Tape Ubi Yang Difermentasikan Selama 3 Hari Dan 6 Hari Yang Dijual Pada Pasar Boro Kecamatan Rumbia Kabupaten Jeneponto - Rahman Y; Jurnal Syarif; Nurul Utami Halimsyah (Jurnal Media Laboran, 2017)
Tapes are favorite doing foods society, middle class and middle class people, these foods contain compounds formed due to alcohol because alcohol yeast fermentation. fermentation is the process of energy production in cells under anaerobic conditions (without oxygen). Purpose of this study are: (1). To determine the alcohol content in potatoes that have fermentation tape for 3 days and 6 days. (2). To determine differences in levels alcohol on tape potato that has been fermented for 3 days and 6 days. Based on observations concluded that. (1). to distinguish a tape that fermented for 3 days and 6 days to see the texture visible on the tape is not the same between the tape that fermented for 3 days and 6 days since the longer the fermentation the increasingly soft texture on the tape would not even shaped potato again later taste the tape will be beruba acidity. (2). alcohol content in fermented cassava tape for 3 days and 6 days have different alcohol levels are highest in the tape that fermented for 3 days is 1.87% and the tape that fermented for 6 days is 2.87% while the lowest alcohol content on tape fermented for 3 days is 1.34% and the tape that fermented for 6 days is 2.11%.